2021
DOI: 10.1186/s40634-021-00342-1
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of irreparable rotator cuff tears with superior capsular reconstruction

Abstract: The treatment of irreparable rotator cuff tears with severe muscle atrophy and fatty infiltration remains a challenge, especially in young patients. Many surgical procedures for these tears have been reported. No one surgical treatment has proven to be an optimal solution. Recently, reconstruction of the superior capsule with an allograft or autograft has gained popularity. In this manuscript, we reviewed the biomechanical and clinical reports that have assessed superior capsular reconstruction and clarified t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“… 11 24) One of the working mechanisms of SCR is the spacer effect, and the graft acts as a spacer to compress the humeral head against the acromion. 25) Mihata et al 24) reported that the graft of fascia lata with 8 mm thickness could provide greater shoulder stability than that of a graft with 4 mm thickness. The difference in shoulder stability provided by grafts with different thicknesses revealed that the graft functions as a spacer.…”
Section: Discussionmentioning
confidence: 99%
“… 11 24) One of the working mechanisms of SCR is the spacer effect, and the graft acts as a spacer to compress the humeral head against the acromion. 25) Mihata et al 24) reported that the graft of fascia lata with 8 mm thickness could provide greater shoulder stability than that of a graft with 4 mm thickness. The difference in shoulder stability provided by grafts with different thicknesses revealed that the graft functions as a spacer.…”
Section: Discussionmentioning
confidence: 99%
“…SCR is indicated with young, active patients with massive rotator cuff tears, have a functional cuff deficiency from a failed a previous rotator cuff repair (Hamada Grade 1 or 2), and no significant glenohumeral arthritis. [3][4][5] The indications for the InSpace balloon (Stryker; Kalamazoo, Michigan) are similar to SCR, although the balloon can be used in patients who may not be able to partake in the extensive SCR rehabilitation. Tendon transfer is utilized in young, non-arthritic, heavy laboring patients who require improved strength.…”
Section: Video Transcriptmentioning
confidence: 99%
“…SCR is indicated with young, active patients with massive rotator cuff tears, have a functional cuff deficiency from a failed a previous rotator cuff repair (Hamada Grade 1 or 2), and no significant glenohumeral arthritis. 3-5…”
Section: Video Transcriptmentioning
confidence: 99%
“… 30 This leads to a significant clinical improvement in biomechanical function and pain at the glenohumeral joint. 17 , 31 …”
mentioning
confidence: 99%
“…Biomechanically, cadaveric studies have largely demonstrated positive results with SCR. 31 The procedure leads to a significant decrease in the superior translation of the humeral head and in subacromial contact pressures. 14 This biomechanical benefit of SCR has translated to the clinical setting with generally positive results.…”
mentioning
confidence: 99%